Cómo crear paquetes en R - García Callejas, David; De la Cruz Rot, Marcelino (Ecosistemas, 2020)
García-Callejas, D., De la Cruz, M. 2019. Cómo crear paquetes de R. Ecosistemas 28(3):1948. https://doi.org/10.7818/ECOS.1948